Children with Autism Spectrum Disorder and Patterns of Participation in Daily Physical and Play Activities - Amir Hossein Memari; Nekoo Panahi; Elaheh Ranjbar; Pouria Moshayedi; Masih Shafiei; Ramin Kordi; Vahid Ziaee (Neurology Research International)
Autism spectrum disorder (ASD) indicates several neurodevelopmental impairments which may end in impairments in motor or physical activities. Daily physical activity involvement was investigated in a total of 83 children (52 boys and 31 girls) with ASD aged 6–15 years. Results indicated that only 10 (12%) of children with ASD were physically active. Children were predominantly engaged in solitary play rather than social play activities. Gender, family income, and household structure were found to be associated with activity scores. Financial burden and lack of opportunities were noted as the leading barriers to physical activities. In conclusion, findings indicated a low rate of physical activity participation in children with ASD that is closely associated with sociodemographic variables.